Quality of life in oncology - Kiebert, Gwendoline M. (Radiology and oncology (Ljubljana), 1997)
Since it has been recognised that QoL is an important autcome in medicine thisfield of research has grown rapidly. In the past decade increasing attention is being given to more systematic and quantitative ways to evaluate explicitly the impact of diseases and medical interventions on QoL. A substantial part of this resarch pertained to the field of cancer where cure is not always possible and treatments are mostly intrusive. The general purpose of QoL assessment in medicine is to provide accurate evaluations of the wellbeing of individuals or groups of patients, and of the benefits and losses that may result from medical interventions. The focus of study can be to describe, to measure changes over time, to compare different populations, or to predict future outcomes. if QoL is to be evaluated, a number of decisions have to be made concerning the methodology of measurement. These decisions relate to: a) the design of the study; b) the components of QoL thatwill be evaluated; c) the instrument(s) to measure the relevant components; d) the subjects and e) the timing of assessment. In recent years it has become more acceptable to include QoL (mostly as a secondary) outcome measure in cancer clinical trials. Since missing QoL forms or missing data are, by definition, irretrievable, logistics and organization of the study require special measures to ensure good quality of data up-front. As QoL research is a rather new field of research there is not yet a large data base available to compose reference scores which can be used to calculate sample size and to facilitate the interpretation of results. In cancer clinical trials QoL is mostly evaluated between treatment arms in a longitudinal design. But what are significant chanbes over time? Surely statistical significance is not identical to clinical significance. (Abstract truncated at2000 characters.)
Keywords: Neoplasms; Quality of life; Survival analysis; Time factors